Impurity-related linear and nonlinear optical response in quantum-well wires with triangular cross section (2013)
ABSTRACT: The 1s-like and 2p-like donor impurity energy states are studied in a semiconductor quantum wire of equilateral triangular cross section as functions of the impurity position and the geometrical size of the structure. Linear and nonlinear coefficients for the optical absorption and relative refractive index change associated with 1s-2p transitions are calculated for both the x-polarization and y-polarization of the incident light. The results show a mixed effect of redshift and blueshift depending on the location of the donor atom. Also, strong nonlinear contributions to the optical absorption coefficient are obtained for both polarizations in the on-center impurity case.